Il delitto perfetto : Strategie dell’immagine tra analogico e digitale - Gurisatti, Giovanni (Scenari, 2021)
According to an iconic ontology which distinguishes ‘pictorial’ (chromography), chemical (photography) and synthetic images (digitography), this essay examines the effects of the Second visual Revolution that from the 1990s onwards marked the transition to the so called post-photographic era, thanks to the prevalence of digital technology over the analog one. This new era is characterized by the endless enhancement of a widespread ‘pictorial’ imagination, by the possibility for everyone to document and manipulate images ‘in real time’, as well as by the limitless increase of everyone’s capacity to create images that are “hyperreal unrealities”, and appear indistinguishable from every ‘real’ image reproducing reality. The high rate of virality of these virtual images raises the problem of an iconic ethics on the web. This problem may be addressed either from a pedagogical or from an aesthetological perspective, in order to develop adequate immunitary defences, both public and personal, against the epidemics infecting the mediasphere.